JUSTICE OR PUNISHMENT? THE DEATH OF OSAMA BIN LADEN IN THE LIGHT OF UTILITARIANISM AND KANTIAN MORAL THEORY - Barbosa Risso, Andrik; Arruda de Moura, Sérgio (LINKSCIENCEPLACE, 2026)
This paper has as its main objective to discuss the operation that led to the death of Osama bin Laden, terrorist leader of the Islamic fundamentalist group Al-Qaeda, and identify the act as justice or punishment based on the foundations of philosophy as the morality of Kant and utilitarianism theory. Interpret the Declaration of Human Rights and understand the functioning of the International Criminal the International Criminal Court, which is responsible for judging and punishing individuals who commit crimes against humanity.